Custom-made 3D printed masks for children using non-invasive ventilation: a feasibility study of production method and testing of outcomes in adult volunteers. (3rd July 2020) - Willox, Matt; Metherall, Peter; Jeays-Ward, Katherine; McCarthy, Avril D.; Barker, Nicki; Reed, Heath; Elphick, Heather E
Abstract: Non-invasive ventilation (NIV) is assisted mechanical ventilation delivered via a facemask for people with chronic conditions that affect breathing. NIV is most commonly delivered via an interface (mask) covering the nose (nasal mask) or the nose and mouth (oronasal mask). The number of children in the UK requiring NIV is currently estimated to be around 5000. Mass-produced masks are available for both the adult and paediatric markets but masks that fit well are difficult to find for children who are small or have asymmetrical facial features. A good conforming fit between the mask and the patient's face to minimise unintentional air leakage is essential to deliver the treatment effectively; most ventilators will trigger an alarm requiring action if such leakage is detected. We present an innovative use of 3D scanning and manufacturing technologies to deliver novel mask-face interfaces to optimise mask fit to the needs of individual patients. Ahead of planned user trials with paediatric patients, the project team trialled the feasibility of the process of creating and printing bespoke masks from 3D scan data and carried out testing of the masks in adult volunteers to select the strongest design concept for the paediatric trial. The evaluation of the process of designing a bespoke mask from scan data, arranging for its manufacture and carrying out user testing has been invaluable in gaining knowledge and discovering the pitfalls and timing bottlenecks in the processes. This allowed the team to iteratively refine the techniques and methods involved, informing user trials later on in the project. It has also provided indicative cost estimates for 3D printed mask prototype components which are useful in project decision making and trial planning. The value of the process extends to considerations for future implementation of the process within a clinical pathway.